Penerapan Kerangka Filosofis (Ontologi, Epistemologi, dan Aksiologi) Untuk Menganalisis dan Meningkatkan Standar Penelitian di Bidang Manajemen - Dedeh Nurdalillah; Daffa Ivandharu; A. Rohendi; Mira Veranita (Indonesian Journal Publisher, 2025)
The philosophy of science provides a crucial bedrock for developing and executing scientific endeavors, particularly within the field of management science. This article conducts a literature review to analyze how the core principles of the philosophy of science specifically epistemology (the study of knowledge), ontology (the study of being/reality), and axiology (the study of values) are applied in management research. Epistemology offers direction on ensuring validity and selecting appropriate data collection methods. Ontology assists researchers in grasping the fundamental nature of organizational reality. Axiology guarantees that the research is conducted ethically and yields important practical contributions. The study also identified several frequently employed methodological approaches in management research, such as positivism, post-positivism, and mixed methods, illustrating the significance of scholarly paradigms in interpreting the intricacies of organizational settings. The results of this analysis have significant implications, including the potential to foster new paradigms in management science and providing actionable guidance for constructing research that is more valid, relevant, and ethically sound. In conclusion, the article argues that the philosophy of science does more than just establish theoretical foundations; it actively enhances the quality of management research, leading to academic work that offers meaningful contributions to both scholars and professionals in organizational settings. Thus, it is advised that the philosophy of science be incorporated into research education and training to enhance the relevance and influence of future research results.